(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the safety and efficacy of using small double-lumen tubes with longitudinal groove structures in open-heart surgery at Hanoi Medical University Hospital from March 2023 to December 2024. Methods: A cohort study was conducted on adult patients undergoing open heart surgery at Hanoi Medical University Hospital from March 2023 to December 2024 with two groups: wide-sided hole tube and fluted tube. Results: There were 154 subjects (71 wide-sided hole tube, 83 fluted tube) with similar age and gender. The two groups underwent surgery for valvular heart disease, coronary artery disease, congenital heart disease with the equivalent time of extracorporeal circulation, and aortic clamp in the two groups. The fluted tube group tended to be safer and more effective in terms of reoperation rate due to cardiac tamponade, less amount of pericardial fluid; shorter number of drainage days and hospital stay. Conclusions: The smaller silicone fluted drainage tubes tend safer, more effective, more convenient to set up and use, contributing to improving the effectiveness of treatment for patients after open heart surgery